PENGARUH MODEL PEMBELAJARAN INQUIRY BERBANTUAN MEDIA WORDWALL TERHADAP HASIL BELAJAR SISWA MATERI WUJUD ZAT DAN PERUBAHANNYA DI KELAS IV SDN 10 KABILA KABUPATEN BONE BOLANGO - Humolungo, Elsa; Abdullah, Gamar; Kudus, Kudus; Arif, Rifda Mardian; Arifin, Irvin Novita (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2025)
This comprehensive study aims to describe and quantitatively investigate whether there is a significant effect of the application of the inquiry learning model integrated with interactive Wordwall media on student learning outcomes, especially on the material of the state of matter and its changes, in the fourth grade environment of SDN 10 Kabila, Bone Bolango Regency. The research method implemented is quasi-experimental with a specific design of Nonequivalent Control Group Design. This design involves a comparison between two pre-existing learning groups, namely the experimental class that received special treatment in the form of an inquiry learning model assisted by Wordwall media, and the control class that followed conventional learning. Data collection was carried out through three main techniques: observation to directly observe the learning process and student interactions, learning outcome tests in pre-test and post-test formats to measure students' understanding of the material before and after the intervention, and documentation to collect relevant supporting data. The research sample consisted of 34 third grade students of SDN 10 Kabila. Analysis of learning outcomes showed clear differences: in the pre-test, the control class obtained an average score of 40, which then increased to 56.47 in the post-test. Meanwhile, the experimental class, which implemented the inquiry model assisted by Wordwall media, started with an average pre-test score of 38.82 and showed a very significant spike in achievement in the post-test with an average score reaching 84.51. Based on these results, it can be concluded that there is a positive and substantial influence of the use of the inquiry learning model integrated with interactive Wordwall media on improving student learning outcomes on the material on the state of matter and its changes in class IV SDN 10 Kabila. ABSTRAKPenelitian ini secara komprehensif bertujuan untuk mendeskripsikan dan menginvestigasi secara kuantitatif apakah terdapat pengaruh signifikan dari penerapan model pembelajaran inkuiri yang diintegrasikan dengan media interaktif Wordwall terhadap hasil belajar siswa, khususnya pada materi wujud zat dan perubahannya, di lingkungan kelas IV SDN 10 Kabila, Kabupaten Bone Bolango. Metode penelitian yang diimplementasikan adalah quasi experimental dengan desain spesifik Nonequivalent Control Group Design. Desain ini melibatkan perbandingan antara dua kelompok belajar yang telah ada sebelumnya, yaitu kelas eksperimen yang menerima perlakuan khusus berupa model pembelajaran inkuiri berbantuan media Wordwall, dan kelas kontrol yang mengikuti pembelajaran konvensional. Pengumpulan data dilaksanakan melalui tiga teknik utama: observasi untuk mengamati secara langsung proses pembelajaran dan interaksi siswa, tes hasil belajar dalam format pre-test dan post-test untuk mengukur pemahaman siswa terhadap materi sebelum dan sesudah intervensi, serta dokumentasi untuk mengumpulkan data pendukung yang relevan. Sampel penelitian terdiri dari 34 siswa kelas III SDN 10 Kabila. Analisis hasil belajar menunjukkan perbedaan yang jelas: pada pre-test, kelas kontrol memperoleh nilai rata-rata 40, yang kemudian meningkat menjadi 56,47 pada post-test. Sementara itu, kelas eksperimen, yang menerapkan model inkuiri berbantuan media Wordwall, memulai dengan nilai rata-rata pre-test sebesar 38,82 dan menunjukkan lonjakan capaian yang sangat signifikan pada post-test dengan nilai rata-rata mencapai 84,51. Berdasarkan hasil tersebut, dapat ditarik kesimpulan kuat bahwa terdapat pengaruh positif dan substansial dari pemanfaatan model pembelajaran inkuiri yang diintegrasikan dengan media interaktif Wordwall terhadap peningkatan hasil belajar siswa pada materi wujud zat dan perubahannya di kelas IV SDN 10 Kabila.